Pengembangan Multimedia Powerpint berbasis quided inquary learning pada materi reaksi reduksi oksidasi terhadap kemampuan berfikir tingkat tinggi siswa kelas X IPA SMA/MA - Isramil Husna; Syamsi Aini; Hardeli Hardeli; Ananda Putra (Postgraduate, University of Mataram, 2022)
The purpose of this research is to develop a powerpoint media for oxidation and reduction reactions based on quided inquiry learning towards high-level thinking abilities of X-grade Senior High School students. The model used is the RND (Research and Development) development model with the 4D method, namely the stages of definition (Define), design (Design), development (Develop) and dissemination (Disseminate). The limitation of this research is only up to the development stage. This development assessment is valid and practical. There are two categories of validation, namely material validation with content, construct, linguistic and graphic validation elements, while media expert validation uses display and media elements. Elements of practice can be seen from the questionnaire conducted by 36 students and 2 teachers. The results of this study are powerpoint media that meet valid and practical criteria, so that they can be used for learning oxidation and reduction reactions to high-level thinking skills in senior high school